“People Will Say That I Am Proud”: A Qualitative Study of Barriers to Bed Net Use away from Home in Four Ugandan Districts - Monroe, April; Harvey, Steven A.; Lam, Yukyan; Muhangi, Denis; Loll, Dana; Kabali, Asaph Turinde; Weber, Rachel (Malaria journal, 2014)
Despite increased access and ownership, barriers to insecticide-treated bed net (ITN) use persist. While barriers within the home have been well documented, the challenges to net use when sleeping away from home remain relatively unexplored. This study examines common situations in which people sleep away from home and the barriers to ITN use in those situations.To explore these issues, a group of researchers conducted 28 in-depth interviews and four focus groups amongst adults from net-owning households in four Ugandan districts.In addition to sleeping outside during hot season, participants identified social events, livelihood activities, and times of difficulty as circumstances in which large numbers of people sleep away from home. Associated challenges to ITN use included social barriers such as fear of appearing proud, logistical barriers such as not having a place to hang a net, and resource limitations such as not having an extra net with which to travel. Social disapproval emerged as an important barrier to ITN use in public settings.Unique barriers to ITN use exist when people spend the night away from home. It is essential to identify and address these barriers in order to reduce malaria exposure in such situations. For events like funerals or religious “crusades” where large numbers of people sleep away from home, alternative approaches, such as spatial repellents may be more appropriate than ITNs. Additional research is required to identify the acceptability and feasibility of alternative prevention strategies in situations where ITNs are unlikely to be effective.
Keywords: Malaria, Insecticide-Treated Bednet, Sleeping outdoors, Barriers, Net use, Qualitative research, Funerals, Conflict, Uganda